Tempo máximo de fonação, autopercepção de fadiga corporal, sintomas e desvantagem vocal após Covid-19 - Britz, Deisi Luana (2023)
Introduction: COVID -19 can cause disorders in the respiratory system and vocal tract, both of which are involved in voice production. Purpose: To perform an analysis and comparison of the maximum phonation times of /ė/ and /e/, self-perception of physical fatigue, vocal symptoms, and vocal impairment of subjects after orotracheal intubation due to COVID -19, by sex and age group, and to compare with a group of subjects without orotracheal intubation after COVID -19 infection and with reference values. Methods: An evaluation of post- COVID -19 in adult and elderly subjects of both sexes took place. The maximum phonation time of /e/ and /ė/, the functional assessment of chronic disease therapy, the Vocal Symptom Scale, and the Vocal Handicap Index were evaluated. The assumed significance level was 0.05%. Results: In intubated women aged up to 60 years, there was significance in all Vocal Handicap Index scores, with the emotional score outside normal values, and significance in all Vocal Symptoms Scale scores, with the total score outside normal values. There was a positive correlation between the maximum phonation time and a negative correlation between the maximum phonation time of /e/ and the vocal selfassessment instruments. Conclusion: Women aged up to 60 years who underwent intubation had abnormalities in the Vocal Symptoms Scale and the Vocal Handicap Index, suggesting that OTI is an exacerbating factor for deprivation and the presence of vocal symptoms in the period after COVID -19. When the values of these instruments were higher, the maximum phonation time of /e/ was lower, suggesting that possible glottal source interference reflected this variable.